Influência do sexo no perfil bioquímico sérico de (Cairina moschata) e (Pavo cristatus) em ambiente de zoológico - Souza, Rafael Rocha de (2018)
The dissertation was divided into three chapters and follows the guidelines of the Graduate Program in Veterinary Science. In the first chapter, the general considerations are included, in which aspects of taxonomy, feeding, reproduction, habits, geographical distribution and clinical biochemistry of birds will be discussed. In the second chapter entitled "Influence of sex on the serum biochemical profile of Cairina moschata in a zoo environment", it is structured as a scientific article which includes, abstract, introduction, material and methods, results, discussion and references. The objective of this study was to determine the influence of sex on serum concentrations of total proteins, albumin, globulins, albumin / globulin, cholesterol, triglycerides, urea, creatinine, creatine phosphokinase, calcium, phosphorus, calcium / phosphorus, magnesium, aspartate aminotransferase, alanine aminotransferase, gamma glutamyl transferase, alkaline phosphatase, uric acid. This article will be sent for publication in the journal Acta Veterinária Brno, after the corrections and suggestions proposed by the examining bank. In the third chapter entitled "Influence of sex on the serum biochemical profile of the Indian peacock (Pavo cristatus) in a zoo environment", it has the same structure as the second chapter, evaluating the influence of sex on the same serum biochemical elements. This article will be sent for publication in the journal Acta Veterinária Brno, after the corrections and suggestions proposed by the examining bank.